Konsep punishment dalam pendidikan Islam PERSPEKTIF manuskrip H. ISMAIL ARSYAD - Natasya Camelawaty; Sukino Sukino; Muh Gitosaroso (PIONIR: JURNAL PENDIDIKAN, 2025)
This study aims to examine the concept of punishment in Islamic education based on a few manuscripts on Islamic education written by H. Ismail Arsyad. This research employs a qualitative library research approach, with the manuscript as the primary data source, supported by relevant literature. Data were analyzed using thematic content analysis to identify key ideas related to the educational purpose, principles, and implementation of punishment in Islamic education. The findings reveal that punishment, according to H. Ismail Arsyad, is conceptualized as an educational and corrective instrument intended to shape students’ moral behavior rather than as a repressive form of discipline. His perspective emphasizes justice, proportionality, and wisdom, while explicitly rejecting physical punishment in educational settings. This study contributes to Islamic education scholarship by highlighting a manuscript-based perspective from a local Islamic education figure, thereby enriching existing discussions on humane and character-oriented disciplinary practices in Islamic education. Keywords: Punishment, Islamic Education, Manuscripts, Ismail Arsyad